Resource aware space mission routing - Ibrahim, Sameh Abdelfattah Abdelghany (AUC Knowledge Fountain, 2019)
In space applications, the mission lifetime is considered one of the most crucial issues. Such missions rely mainly on rovers that move around to sense useful information to be later sent to the earth. The main source of energy in such applications is the solar energy at daytime and then batteries are the only source available at night operation. Due to the scarcity of energy on Mars, a careful design is needed at all levels of the mission to save the energy consumption. The rover communication system consumes a considerable amount of energy during the mission. The used routing protocol can have a huge effect on the energy consumed during the communication between the rovers. Thus, an efficient routing protocol that can effectively exploit the rover resources, and most importantly its energy, is needed. In this thesis, a resource aware routing protocol that will help in extending the lifetime of Mars exploration missions is proposed. The simulation results run on MATLAB have shown that the proposed space mission routing protocol increases the lifetime of the mission, the fairness between the rovers and the packet delivery ratio. In addition to the introduction of the space mission routing, further techniques were implemented to guarantee that the system lifetime is at its maximum. The optimal initial positions of the rovers were obtained resulting in an extended mission lifetime. Furthermore, the bottleneck orbit was identified, and countermeasures were taken to achieve the highest mission lifetime possible. The simulation results obtained showed that the additional two techniques resulted in a much higher lifetime of the mission.